Comparative effects of technical toxaphene, 2,5-dichloro-3-biphenylol and octabromodiphenylether on cell viability, [Ca2+], levels and membrane fluidity in mouse thymocytes - Sandal, S; Yilmaz, B; Chen, CH; Carpenter, DO (Elsevier Ireland Ltd, 2004)
Flow cytometric studies of mouse thymocytes show that technical toxaphene (10-20 ppm) and 2,5-dichloro-3-biphenylol (PCB 9-OH) (5-10 ppm) kill cells and cause an increase in intracellular calcium concentration, [Ca2+](i), whereas commercial octabromodiphenylether (OBDE) has no effect. The cell death is not a result of the rise of [Ca2+](i), since the divalent cation ionophore, ionomycin, causes a large elevation in [Ca2+](i) without cell death. We have studied effects of these compounds on membrane fluorescence polarization, a measure of membrane fluidity, using 1,6-diphenyl-1,3,5-hexatriene (DPH). We find that toxaphene causes a decrease in membrane fluidity in the concentration range associated with cell death, whereas PCB 9-OH causes an increase in fluidity and OBDE has no effect. These observations suggest that alterations of membrane fluidity of thymocytes, whether it be an increase or decrease, can cause cytotoxicity. (C) 2004 Elsevier Ireland Ltd. All rights reserved.
Keywords: flow cytometry; PCBs; organoltalogenated compounds